2012
DOI: 10.2174/187153012799279117
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Echinococcosis: Aspects of Immune Response, Immunopathogenesis and Immune Evasion from the Human Host

Abstract: Cystic echinococcosis (CE) is a neglected infectious disease caused by the larval stage of Echinococcus granulosus. It constitutes a major public health problem in developing countries. During CE, the distinguishing feature of the host-parasite relationship is that chronic infection coexists with detectable humoral and cellular responses against the parasite. In order to establish successfully an infection, E. granulosus releases molecules that directly modulate the host immune responses favoring a strong anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 51 publications
3
52
0
1
Order By: Relevance
“…Todorov et al in 1976 have shown that the values of the indirect hemaglutination remained elevated in 80% of patients, four years after resection of the cyst [25] . However Ortona et al and Siracusano et al [26,27] reported on an "immunoblot" analysis revealed anti-HSP20 (Heat Shock Protein 20) antibodies in a statistically significant higher percentage of sera from patients with active disease than in sera from patients with inactive disease. This antibody seems to be a potential marker of active CE.…”
Section: Resultsmentioning
confidence: 99%
“…Todorov et al in 1976 have shown that the values of the indirect hemaglutination remained elevated in 80% of patients, four years after resection of the cyst [25] . However Ortona et al and Siracusano et al [26,27] reported on an "immunoblot" analysis revealed anti-HSP20 (Heat Shock Protein 20) antibodies in a statistically significant higher percentage of sera from patients with active disease than in sera from patients with inactive disease. This antibody seems to be a potential marker of active CE.…”
Section: Resultsmentioning
confidence: 99%
“…The immunology of CE has been reviewed . Like in other helminth infections, the host effector response in CE is Th2‐biased .…”
Section: Immune Responses In Cementioning
confidence: 99%
“…In order to establish successfully an infection, E. granulosus releases molecules that directly modulate the host immune responses favoring a strong anti-inflammatory response and perpetuating parasite survival in the host [7]. It constitutes a major public health problem in developing countries.…”
Section: Editorialmentioning
confidence: 99%